STRATEGI ALIANSI RUSIA - SURIAH DALAM MENGHADAPI KELOMPOK PEMBERONTAK DAN TERORIS PERIODE 2015-2017 - Abdul Ghofar Dwi Prawira, - (2018)
The Syrian civil war that occurred has attracted the world's spotlight on the country, this is because in the civil war that occurred not only between the government and the rebels, but also the presence of other parties such as Russia, America and even ISIS. this study aims to analyze and study how the alliance strategy between Russia and Syria in the face of insurgent groups and Terrorists in 2015-2017. This approach is qualitative. The type of research used is applied and descriptive. The data source used is primary and secondary data which is done through literature study. The data will be analyzed using national interest theory, alliance theory and strategy concept, while to clarify there is also the concept of terrorist and rebel. Based on data analysis conducted, it can be concluded that the strategy undertaken by Russian alliance with Syria in the form of sending aid of fleet of sea, land and air. And Russia plays an active role in the fight against insurgent groups and terrorists